Marker-assisted selection for bacterial leaf blight resistance in MR219 × IRBB60 rice (Oryza sativa L.) variety - Mohd Zuki, Zakiah (2018)
Rice is one of the most important food sources for more than half the world population, which its yield constantly affected by more than 70 diseases. Bacterial leaf blight (BLB) is a major problem in rice production across the world including Malaysia. One of the main reasons was lack of BLB resistant varieties were planted for commercial cultivation in Malaysia. Marker-assisted selection (MAS) has been proven to be useful in breeding and development of variety resistance in rice. Therefore, the main objective of this study was to develop BLB resistance rice lines using simple sequence repeat (SSR) markersassisted selection between resistant BLB rice line (IRBB60) and high yielding but susceptible variety (MR219). The specific objectives were to determine highly BLB resistant near isogenic lines for crossing program, to identify SSR markers associated with BLB resistance R-gene, to quantify phenotypic and genotypic inheritance resistance pattern of the R-gene in F2 rice population and to select BLB resistant lines in the F2 population. From nine near isogenic BLB resistant lines, IRBB60 was the most resistance to BLB disease in local environment. This line was used to cross with high yielding local variety, MR219 for development of BLB resistant variety. For genotyping segregation analyses, a total of 129 SSR markers were tested on parental lines MR219 × IRBB60 for BLB resistance, and only 42 (32%) SSR primers show distinct polymorphism. Out of the 42 polymorphic markers, the best 18 including R-gene based markers were used to screen on 345 F2 progenies for resistance to bacterial leaf blight. The patterns of all the 15 markers were similar with segregation ratio is 1:2:1 except the others 3 markers (RM400, RM264 and RM281). The chi-square analysis (χ2) confirmed that the genotypic ratio shows a good fit to expected Mendelian segregation ratio (1:2:1) for 15 SSR markers, RM13 (xa5), RM21 (Xa21), RM122 (xa5), RM153 (xa5), RM164 (Xa13), RM206 (Xa10), RM5509, RM20B, RM25, RM163, RM169, RM218, RM267, RM276, and RM334, for a single gene model (d.f. =2.0, p≤0.05). For phenotypic ratio, the F2 population segregated in a 3:1 (R:S) for resistant and susceptible plants, respectively. This indicated that resistance to bacterial leaf blight caused by pathotype Xoo P7.0 in the MR219 × IRBB60 F2 population is controlled by single dominant genes. Seventy-five highly resistant lines derived from MR219 × IRBB60 consist of four BLB R-genes (xa5, Xa10, Xa13 and Xa21) in the homozygous form were identified for further evaluation.The result indicated that a significant finding of this rice breeding program using MAS for development of high yield with durable bacterial leaf blight resistance in Malaysia.